From Strategy and ESG to Shareholder Value: The Mediating Role of Sustainable Financial Performance and The Moderating Effect of Shariah Value Added in Indonesia - Agung Budi Sulistiyo; Novi Wulandari Widiyanti; Imamatin Listya Putri; Muhammad Miqdad (Universitas Swadaya Gunung Jati, 2025)
This study examines the effects of corporate strategy, ESG performance, investment efficiency, and risk management on shareholder value in Indonesian publicly listed companies. It also investigates the mediating role of sustainable financial performance and the moderating role of Shariah Value Added. Using panel regression on data from 72 firms between 2019 and 2022, the findings show that only corporate strategy significantly enhances sustainable financial performance. ESG performance, investment efficiency, and risk management do not show meaningful effects, indicating that many firms focus on meeting ESG compliance requirements rather than integrating ESG strategically. Sustainable financial performance also does not directly increase shareholder value. However, when moderated by Shariah Value Added, its effect becomes significant. This demonstrates that Islamic ethical principles can strengthen corporate legitimacy, enhance investor trust, and bridge financial outcomes with ethical values. These findings enrich legitimacy theory by incorporating cultural and religious dimensions into sustainability research. Practically, companies should integrate ESG more substantively, while regulators are encouraged to consider including Shariah-based indicators in sustainable finance frameworks. The study’s limitations include a relatively small sample size and a short observation period. Future research should extend the timeframe and explore additional variables that may influence these relationships.